2010
DOI: 10.2460/ajvr.71.7.750
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-like receptors 2 and 4 in stifle joint synovial tissues of dogs with or without osteoarthritis

Abstract: Increased TLR-4 gene expression in the synovial tissue of SJs with osteoarthritis secondary to CrCLt suggests that activation of innate immunity may play a role in the pathophysiology of SJ osteoarthritis in at least a subset of dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Zhang et al showed that activation of different TLRs had a differential effect on collagenase gene expression [153]. TLR-4 gene expression was increased in the synovial tissue of stifle joints with OA induced by cranial cruciate ligament transection in dogs, but expression of TLR-2 remained unchanged [154]. MyD88 dependent TLR2/TLR4 signaling was demonstrated as crucial in mediating catabolic responses to low molecular weight hyaluronan (LMW-HA) and HMG-B1 in murine cartilage explants [155].…”
Section: Major Signaling Pathways Involved In Oamentioning
confidence: 99%
“…Zhang et al showed that activation of different TLRs had a differential effect on collagenase gene expression [153]. TLR-4 gene expression was increased in the synovial tissue of stifle joints with OA induced by cranial cruciate ligament transection in dogs, but expression of TLR-2 remained unchanged [154]. MyD88 dependent TLR2/TLR4 signaling was demonstrated as crucial in mediating catabolic responses to low molecular weight hyaluronan (LMW-HA) and HMG-B1 in murine cartilage explants [155].…”
Section: Major Signaling Pathways Involved In Oamentioning
confidence: 99%
“…TLRs have been found to have important roles in several canine diseases such as anal furunculosis (House et al 2008), osteoarthritis (Kuroki et al 2010), inflammatory bowel disease (McMahon et al 2010) and pyometra (Chotimanukul and Sirivaidyapong, 2011) to name a few. Investigations into the importance of TLRs in CanL are ongoing, but at present preliminary.…”
Section: Tlrsmentioning
confidence: 99%
“…In the canine patient the role of TLR4 during sepsis and the related systemic inflammatory response syndrome has still not been investigated. However, a potential role of TLR4 in dogs with osteoarthritis [40] and chronic enteropathies [20] was proven.…”
Section: Discussionmentioning
confidence: 99%